(cos13°+sin 13°) /(cos13°-sin13°) [(cos13°+sin 13°)/cos13°] /[(cos13°-sin13°)/cos13°] =(1+tan13°)/ (1-tan13°) Put tan 45° in place of 1. =(tan45°+tan13°)/(1-tan13°×tan45°) Using the tangent addition formula: tan(a+b) =(tanA+tanB)/ (1-tanA.tanB) =tan (45°+13°) =tan (58°)
21 24 22 25 23 ?
...8 12 39 ? 180 216
...2 3 5 9 ? 33
...What will come in place of the question mark (?) in the following series?
1.5, 3.5, 9.5, 27.5, 81.5, 243.5, ?
22, 37, 63, 98, 148, ?
32, 64, 144, ?, 990, 2970
32, 52, 82, 124, 180, ?
18 ? 20 13 22 11
15, 8, 9, 15, 32, ?
50, 49.5, ?, 45.5, 42, 37.5